Simulation / Wong Chee Weng (Universiti Teknologi MARA, Sarawak, 1992)
Simulation analysis is a natural and logical extension of the analytical and mathematical models inherent in operational research. Many situations cannot be represented mathematically because of the stochastic nature of the problem, the complexity of the problem formulation, or the interactions needed to adequately describe the problem under study. For many situations defying mathematical formulation, simulation is the only tool that might be used to obtain the relevant answers. Simulation, a numerical technique for conducting experiments on a digital computer involves the interaction of logical and mathematical relationships to describe the behaviour and structure of a complex real-world system over extended periods of time. In short, simulation has often been described as the process of creating the essence of reality without ever actually attaining that reality itself.